Experiences of patient violence on staff in acute in patient psychiatric units a case study of Gweru provincial hospital - Mambende, Sheila (Midlands State University, 2018)
Nurses working in acute inpatient psychiatry experience high rates of violence perpetrated by patients. Their perspectives, attitudes and feelings towards the phenomena are essential to understand the phenomena of patient violence the purpose of this study was to explore and describe in detail the experiences of patient violence directed towards staff in acute inpatient psychiatric unit at Gweru Provincial Hospital. This study particularly explore the registered mental nurses` attitudes and feeling towards patient violence. In this interpretive, descriptive study, a purposeful sample of 12 nurses were interviewed to understand how they feel and perceive their experience of violence within the workplace. A qualitative explorative and descriptive study design was used in this study by sampling only nurses who had experienced violence. Semi structured individual interviews were conducted. Data was presented using thematic content analysis. Experiencing patient violence had many perceived negative impacts on nurses though some had feelings that it was part of their job. A conceptual framework of resiliency was used in the study which correlates with the nurses` ability to endure, survive and thrive after adverse assaultive events. The study found that the participants had mixed feelings and perspectives towards the phenomena. Some experienced and mature nurses had positive attitudes towards patient violence and perceived it as part of their job, while the young and inexperienced nurses had negative attitudes towards patient violence and perceived it as an abuse or workplace harassment. Power, control and stigma also influenced nurses` perceptions and responses to patient violence. In their practices nurses used a wide variety of interventions to stay safe as well as preventing and managing patient violence. Registered mental nurses recommended increased education, resiliency and support as well as improved working environment. Future research should explore the impact of patient violence on patients and patientcare.